2004
DOI: 10.22358/jafs/73948/2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA for nutrient transporters in the gastrointestinal tract before and after weaning

Abstract: We investigated mRNA expression of the glucose transporter, SGLT1, and the long-chain fatty acids translocase, CD36, in the gastrointestinal tract of cattle and goats before and after weaning. SGLT1 and CD36 expression in the jejunum was highest in the gastrointestinal tract before weaning, but it decreased in the small intestine after weaning in both species. From these results, we conclude that the jejunum is likely to be the major absorption site for glucose and long-chain fatty acids before weaning, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It was demonstrated that the weaning of calves and goats reduces the expression of the sodium-dependent glucose transporter 1 and CD36 (a fatty acid transporter; Hayashi et al, 2004Hayashi et al, , 2005 as well as leptin (Yonekura et al, 2002) in the gastrointestinal tract. The salivary secretion rate (Sasaki, 1968) and the activity of carbonic anhydrase in the parotid gland (Kitade et al, 2002) in calves are increased around weaning.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the weaning of calves and goats reduces the expression of the sodium-dependent glucose transporter 1 and CD36 (a fatty acid transporter; Hayashi et al, 2004Hayashi et al, , 2005 as well as leptin (Yonekura et al, 2002) in the gastrointestinal tract. The salivary secretion rate (Sasaki, 1968) and the activity of carbonic anhydrase in the parotid gland (Kitade et al, 2002) in calves are increased around weaning.…”
Section: Introductionmentioning
confidence: 99%